Horizontal gaze-evoked nystagmus in pontine gaze palsy: patterns and anatomical correlates - Choi, Seo-Young; Choi, Jae-Hwan; Kim, Hyun Sung; Lee, Ju-Young; Lee, Sun-Uk; Lee, Seung-Han; Kim, Jae-Myung; Kim, Hyun Ah; Park, Ji-Yun; Choi, Kwang-Dong (Frontiers in Neurology, 2025)
BackgroundTo delineate the patterns and anatomical correlates of gaze-evoked nystagmus (GEN) in horizontal gaze palsy due to dorsal pontine lesions.MethodsA total of 17 patients with horizontal gaze palsy and unilateral dorsal pontine lesions were retrospectively recruited from referral-based six university hospitals in Korea. The clinical characteristics, oculographic data, and MRI lesions of the patients were subjected to analysis.ResultsPatients had complete (n = 10, 60%) or partial (n = 7, 40%) horizontal gaze palsy. Ten patients (60%) showed contralesional horizontal-torsional spontaneous nystagmus. Horizontal GEN was identified in 14 of the 17 patients (82%), which was contralesional (n = 8, 57%), bilateral (n = 5, 36%), and ipsilesional (n = 1, 7%). The lesion overlays revealed that damage to the surrounding area of the abducens nucleus was responsible for the generation of GEN in patients with pontine gaze palsy.ConclusionHorizontal GEN is a common manifestation of pontine gaze palsy. In lesions in the vicinity of the abducens nucleus, the selective or extensive disruption of the connections between the ipsilateral or contralateral horizontal neural integrators and the abducens nucleus may result in diverse patterns of horizontal GEN.